Spermatological characters in Bothriocephalidea (Cestoda) - Šípková, Lenka (Jihočeská univerzita, 2011)
Spermiogenesis and ultrastructure of the spermatozoon of two bothriocephalidean cestodes, Oncodiscus sauridae and Senga sp., have been studied using transmission electron microscopy. The presence of a classical pattern for spermatological characters (spermiogenesis of type I with dense-material in early stages and sperm of type II with a characteristic ring of cortical microtubules in the anterior part) in Bothriocephalidea is discussed.
Spermatological characters in Bothriocephalidea (Cestoda)
Keywords: cestode; spermatozoon; spermiogenesis; transmission electron microscopy